2009
DOI: 10.1002/ab.20336
|View full text |Cite
|
Sign up to set email alerts
|

Peer and cyber aggression in secondary school students: the role of moral disengagement, hostile attribution bias, and outcome expectancies

Abstract: The present study investigated the relationship between cognitive mechanisms applied by people to rationalize and justify harmful acts, and engagement in traditional and cyber bullying among school children. We examined the contribution of Moral Disengagement (MD), Hostile Attribution Bias, and Outcome Expectancies and we further explored the individual contribution of each MD mechanism. Our aim was to identify shared and unique cognitive factors of the two forms of bullying. Three hundred and thirty nine seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
287
4
29

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(354 citation statements)
references
References 82 publications
22
287
4
29
Order By: Relevance
“…Our finding is line with a study by Bauman and Pero (2011), which also reported non-significant associations. However, other studies such as Pornari and Wood (2010) or Bauman (2010) did find significant associations between cyberbullying and moral disengagement. These inconsistencies may be related to different measures and certainly need further exploration in future research.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our finding is line with a study by Bauman and Pero (2011), which also reported non-significant associations. However, other studies such as Pornari and Wood (2010) or Bauman (2010) did find significant associations between cyberbullying and moral disengagement. These inconsistencies may be related to different measures and certainly need further exploration in future research.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have shown that bullying is positively associated with self-reported moral disengagement in adolescents (Hymel, Rocke-Henderson, & Bonanno, 2005;Obermann, 2011) and in children (Gini, 2006;Gini, Pozzoli, & Hauser, 2011). A recent study by Pornari and Wood (2010) showed that moral disengagement is not only associated with traditional peer aggression but also with cyber aggression. A few studies have also used production measures to assess children's and adolescents' moral disengagement strategies and their associations with bullying.…”
Section: Moral Disengagement and Bullyingmentioning
confidence: 99%
“…Consistent with the first suggestion, Hymel, Rocke-Henderson, and Bonanno (2005) found that the more victimization students experienced the fewer morally disengaged strategies they endorsed. Similarly, Pornari and Wood (2010) found a greater number of peer victimization experiences was associated with lower moral disengagement, when controlling for own aggressive behaviour. By contrast, two studies found no differences between (non-aggressive) victims and non-involved children/adolescents with respect to moral reasoning (Gini, 2006;Menesini, Sanchez, & Fonzi et al, 2003).…”
Section: Psychopathy and Moral Disengagementmentioning
confidence: 82%
“…Moral disengagement has been positively related to aggression (Bandura, Barbaranelli, Caprara, & Pastorelli, 1996;Bandura, Caprara, Barbaranelli, & Pastorelli, 2001;Paciello, Fida, Tramontano, Lupinetti, & Caprara, 2008;Pelton, Gound, Forehand, & Brody, 2004;Pornari & Wood, 2010), including bullying behavior (Gini, Pozzoli, & Hauser, 2011;Hymel, Rocke-Henderson, & Bonanno, 2005;Menesini et al, 2003;Obermann, 2011b;Perren et al, 2012), and negatively related to prosocial behavior (Bandura et al, 1996(Bandura et al, , 2001). Gini (2006) found that students who were peer-nominated as bullies, assistants or reinforcers, demonstrated higher moral disengagement than defenders.…”
Section: Moral Disengagementmentioning
confidence: 99%